Hadith About Jinayah Qishash (Murder and Persecution) - Ahmad Baqi; Zakaria Ahmad Marpaung (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study examines hadiths related to qisas (retribution for murder and assault), a criminal act involving murder and assault from an Islamic legal perspective. The purpose of this study is to analyze the content of the hadith, its historical context, and its relevance to the application of qisas law. The method used is a literature study with a normative approach, through a review of hadith books and classical and contemporary fiqh literature. The results show that the hadiths on qisas emphasize the principle of justice, balance between the rights of victims and perpetrators, and open up room for forgiveness as an alternative solution. Furthermore, the concept of qisas in the hadith functions not only as a form of punishment but also as a preventive measure to protect human life. Thus, understanding the hadiths on qisas (retribution for murder) is crucial in building a just and welfare-oriented legal system.